2021
DOI: 10.4149/bll_2020_017
|View full text |Cite
|
Sign up to set email alerts
|

Increasing incidence of type 1 diabetes mellitus in young children in Slovakia

Abstract: OBJECTIVES: We aimed to study the prevalence of the early onset Type 1 diabetes in Slovakia during the years 1996-2017. BACKGROUND: Prevalence of Type 1 diabetes in young children is increasing worldwide. However, recent data from Slovakia are missing. METHODS: All children with newly diagnosed Type 1 diabetes included in the study were diagnosed in the Children Diabetes Centre in Bratislava during the years 1996-2017. The incidence of T1D in children aged below 3 and below 5 years was calculated and compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Some studies have shown a seasonality to the presentation of the GD with the theory of molecular mimicry, which happens when the human body produces self-antigens in response to a viral or bacterial exposure, raising the question of infectious triggers to the disease ( 2 ). Several reports have found an increasing prevalence of autoimmune disease in the pediatric population over the past decades, especially in type I diabetes mellitus ( 17 , 18 ). The possibility of concomitant other autoimmune disorders must always be considered, as some studies have reported a significant association between autoimmune thyroid disease, GD and HT, with other autoimmune illnesses; notably, type 1 diabetes mellitus and celiac disease ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown a seasonality to the presentation of the GD with the theory of molecular mimicry, which happens when the human body produces self-antigens in response to a viral or bacterial exposure, raising the question of infectious triggers to the disease ( 2 ). Several reports have found an increasing prevalence of autoimmune disease in the pediatric population over the past decades, especially in type I diabetes mellitus ( 17 , 18 ). The possibility of concomitant other autoimmune disorders must always be considered, as some studies have reported a significant association between autoimmune thyroid disease, GD and HT, with other autoimmune illnesses; notably, type 1 diabetes mellitus and celiac disease ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…Older people with T1D experience an increased risk of severe hypoglycemia (due to a combination of factors including reduced awareness of hypoglycemic warning symptoms and increased response time) and are therefore viable candidates for CGM, SAP, and HCL systems. Expanding coverage of SAP to near full reimbursement for children with diabetes could also prove useful in Slovakia, with an increasing proportion of pediatric individuals diagnosed with T1D, meaning a substantial number of individuals will require almost lifelong treatment and management programs [ 92 ]. Moreover, expanding coverage of expert telemedicine to people with T1D living in rural areas could overcome barriers to care should development of nearby, dedicated diabetes centers prove untenable.…”
Section: Barriers To Technology Use In Type 1 Diabetesmentioning
confidence: 99%